Height and surfacing as risk factors for injury in falls from playground equipment: a case-control study. Issue 2 (June 1996) - Chalmers, D. J.; Marshall, S. W.; Langley, J. D.; Evans, M. J.; Brunton, C. R.; Kelly, A. M.; Pickering, A. F.
Abstract : OBJECTIVES: Despite the widespread promotion of safety standards no epidemiological studies have adequately evaluated their effectiveness in preventing injury in falls from playground equipment. This study evaluated the effectiveness of the height and surfacing requirements of the New Zealand standard for playgrounds and playground equipment. SETTING: Early childhood education centres and schools in two major cities in the South Island of New Zealand. METHODS: Data were collected on 300 children aged 14 years or less who had fallen from playground equipment. Of these, 110 (cases) had sustained injury and received medical attention, while 190 (controls) had not sustained injury requiring medical attention. RESULTS: Logistic regression models fitted to the data indicated that the risk of injury being sustained in a fall was increased if the equipment failed to comply with the maximum fall height (odds ratio (OR) = 3.0; 95% confidence interval (CI) 0.7 to 13.1), surfacing (OR = 2.3; 95% CI 1.0 to 5.0), or safe fall height (OR = 2.1; 95% CI 1.1 to 4.0) requirements. Falls from heights in excess of 1.5 metres increased the risk of injury 4.1 times that of falls from 1.5 metres or less and it was estimated that a 45% reduction in children attending emergency departments could be achieved if the maximum fall height was lowered to 1.5 metres. CONCLUSIONS: Although the height and surfacing requirements of the New Zealand standard are effective in preventing injury in falls from playground equipment, consideration should be given to lowering the maximum permissible fall height to 1.5 metres.